Preferência do pulgão-preto por feijão-de-corda coletado em estados do Nordeste brasileiro - Nere, Daniel Rodrigues (2016)
The black aphid stands out as one of the most important pests of cowpea, as it causes direct and indirect damages to the plant. A measure of efficient control and easy to use by producers is resistant varieties, which have the ability to reduce infestation or damage caused by this insect. In this sense, this work had the purpose of seeking new sources of cowpea genotypes resistant to black aphid, preserved by farmers, in two distinct regions of the State of Ceará (Cariri and Curu Valley) and landraces collected sparsely in some states of the Northeast. The experiment was conducted in a greenhouse in the UFC-Fortaleza and IFCE - Umirim with a randomized complete block design with four replications, testing seventy-one genotypes distributed in three tests according to the collection area. For comparison, in each assay, were used four genotypes with known resistance. To evaluate the resistance of genotypes, we used the following variables: number of live adults, number of live nymphs and the effective resistance. The results indicated 10 highly resistant genotypes: Rabo-de-tatu (CCE-115), Corujinha (CCE-055), Leandro-do-monte (CCE-112), Paulistinha (CCE-068) Branco-do-marinheiro (CCE-078), Costela-de-vaca (CCE-046), Recife-marrom (CCE-094) Rabo-de-peba (CCE-118), Moitinha (CCE-077) and Passo II (SCC-091), which represent a source resistance to black aphid and may be used in genetic improvement of the cowpea around the world, through backcrossing. Finally, it was found that in all regions studied, there was found cowpea genotypes resistant to Aphis craccivora and, independent of the area, where they were collected, it was found genetic diversity. The mechanisms involved in genotypes resistance to adult aphids may possible be antibiosis and / or antixenosis and for nymphs the results indicate antibiosis.